(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research is entitled "The Influence of Occupational Safety and Health on Employee Job Satisfaction at PT. Hasrjar Abadi Kupang Branch "The problem of this research is whether there is a positive and significant influence of safety (X1) and occupational health (X2) partially or simultaneously on Employee Job Satisfaction at PT. Eternal Passion Kupang Branch. In this research the author used data collection methods sourced from primary data and secondary data as well as interview and questionnaire data collection techniques, then the data analysis technique used was Multiple Linear Regression. The results of the analysis show that safety (X1) and occupational health (X2) have a positive but not significant influence together on employee job satisfaction (Y) at PT Hasrjat Abadi Kupang Branch. The results of multiple determination (R2) = 0.0961 or 9.61%, meaning that changes in employee job satisfaction are influenced by safety (X1) and occupational health (X2) together amounting to 9.61%, while the remaining 90.39 % influenced by other factors not discussed in this study.